Tunable morphology and band gap alteration of CuO-ZnO nanostructures based photocathode for solar photoelectrochemical cells - Albadarin N.A.; Takriff M.S.; Tan S.T.; Shahahmadi S.A.; Minggu L.J.; Kadhum A.A.H.; Yin W.W.; Salehmin M.N.I.; Alkhalqi E.M.; Hamid M.A.A.; Amin N. (IOP Publishing Ltd, 2023)
Copper; Copper oxides; Crystallite size; Electrochemical cells; Electrolytes; Electrons; Energy gap; II-VI semiconductors; Morphology; Nanorods; Optical band gaps; Optical correlation; Oxide minerals; Photocathodes; Photocurrents; Photoelectrochemical cells; Sodium sulfate; Surface morphology; Zinc oxide; Free-electron density; Hydrothermal methods; Optical band structure; Optical energy band gap; Photocurrent density; Photoelectrochemicals; Tunable morphologies; ZnO nanostructures; Sulfur compounds